Strategic Human Resource Management: A Systematic Literature Review - Shashi Kant; Wako Jio Glgelo; Chalchissa Amentie Kero (RADINKA JAYA UTAMA PUBLISHER, 2023)
In recent years, there has been a significant expansion in the field of strategic HRM. This article synthesizes the literature in this field by doing a meta-review, which is a study of reviews that have addressed different facets of strategic HRM. The authors also discuss conceptual frameworks and empirical findings from studies carried out in the field over the preceding three decades, pointing out methodological issues and challenges in the earlier research. They also analyze contemporary developments in the study of strategic HRM. The author concludes with a meta-review of some interesting literature and important lines of inquiry. PRISMA was used to prefer the systematic and meta-analytic review of available review items.